1994
DOI: 10.1136/adc.70.4.271
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of behaviour disorders in low birthweight infants.

Abstract: Objective -To determine the prevalence of behaviour disorders in low birthweight infants. Design

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
79
1
4

Year Published

1997
1997
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 134 publications
(90 citation statements)
references
References 16 publications
6
79
1
4
Order By: Relevance
“…In addition to autism, low birth weight has been associated with a variety of psychiatric, cognitive, and behavioral problems. [84][85][86][87][88][89][90][91][92][93] Season or month of birth was significantly related to the risk of autism in 6 of 12 studies. Although the seasonal trends varied across studies, March 10,23,60,64 and August 10 were both suggested as birth months associated with an elevated risk of autism.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to autism, low birth weight has been associated with a variety of psychiatric, cognitive, and behavioral problems. [84][85][86][87][88][89][90][91][92][93] Season or month of birth was significantly related to the risk of autism in 6 of 12 studies. Although the seasonal trends varied across studies, March 10,23,60,64 and August 10 were both suggested as birth months associated with an elevated risk of autism.…”
Section: Resultsmentioning
confidence: 99%
“…Conseqüentemente, tem aumentado o interesse sobre a investigação da qualidade de vida e a morbidade desses recém-nascidos 1,2 .…”
Section: Introductionunclassified
“…2 Behavioral problems in these children mainly manifest in an increased risk for attention-deficit/hyperactivity disorder 3 and internalizing behavioral problems such as withdrawn behavior, 6 although some studies have also found oppositional behavior. 8,9 A large body of evidence has shown that academic underachievement and behavioral problems arise from a deficit in EF, [10][11][12][13] a set of neurocognitive functions such as inhibitory control, working memory, cognitive flexibility, and planning. 14 EF, therefore, has attracted considerable interest, and in very preterm and/or VLBW children executive dysfunction has been reported, suggested to arise from disruptions of cortical and subcortical circuits connecting frontal, striatal, and thalamic regions.…”
mentioning
confidence: 99%